Effect of Resveratrol Combined with Donepezil Hydrochloride on Inflammatory Factor Level and Cognitive Function Level of Patients with Alzheimer's Disease. (25th March 2022) - Fang, Xincui; Zhang, Jing; Zhao, Jianping; Wang, Litao
Abstract : Objective . To explore the effect of resveratrol (RES) combined with donepezil hydrochloride on inflammatory factor level and cognitive function level of patients with Alzheimer's disease (AD). Methods . A total of 90 AD patients treated in our hospital from June 2019 to June 2020 were selected as the study objects and divided into the control group (CG) and experimental group (EG) by the randomized and double-blind method, with 45 cases each. Patients in CG received donepezil hydrochloride treatment, and on this basis, those in EG received additional RES treatment, so as to compare the clinical indicators between the two groups. Results . Compared with CG after treatment, EG obtained significantly higher good rate, MMSE score, and FIM score (P < 0.05 ) and obviously lower clinical indicators and ADAS-cog score (P < 0.001 ), and between CG and EG, no obvious difference in total incidence rate of adverse reactions was observed after treatment (P > 0.05 ). Conclusion . Combining RES with donepezil hydrochloride has significant clinical efficacy in treating AD, which can effectively improve patients' inflammatory factor indicators, promote their cognitive function, and facilitate patient prognosis.